(untitled) (Research, Society and Development, 2022)
Eating behaviors arise from a combination of several factors namely, physiological, emotional, social and genetic, including the prevailing state of the environment that the individual has been exposed to from the commencement of development. Several factors are known to affect the control of eating behaviors, distinguishable by the synergism of the homeostatic and hedonic control mechanisms, which are complementary. While undeniably homeostasis is under the control of the hormonal interchange between the intestine and the brain, the desire to eat is focused on the brain reward system, which includes acquisition and addictions and binge eating. In today’s world, the easy availability of processed foods, high in sugars and fats, which stimulate the reward areas, can flood the brain with neurotransmitters linked to pleasure and happiness. This often results in an uncontrollable desire to eat, technically termed hedonic hunger. A presentation of an integrated perspective of the mechanisms involved in the control of hedonic eating behavior is given. It is crucial to understand these mechanisms, particularly paying attention to the ways the modern food environment induces excessive consumption and its contributions to the present obesity epidemic.